The degree of Intensivity of Solonetzic Process Within the Virgin Soils and Soils with agrogenic transformation in Solonetzic complexes of frores-steppe and dry steppe zones - I. N. Lyubimova; I. A. Salpagarova; V. V. Khan (Бюллетень Почвенного института им. В.В. Докучаева, 2016)
The comparative assessment of the degree of solonetzic processes was conducted for the soils of solonetzic complexes in forest steppe and dry steppe zones. We analized virgin solonetzes and solonetzes affected by the agrogenic transformation with different content of exchangeable sodium and with different hydromorphism degree from Kostanai (Kazakhstan Republic), Astrakhan, Voronezh, Volgograd, Omsk, and Novosibirsk regions. We investigated meliorated solonetzes as with completely destructed profile, and with partically preserved solonetzic layer. For that purposes we used special B- grade, suggested by N.B. Khitrov. It is shown that solonetzic process is poorly manifested in virgin automorphic soils of dry steppe zone. The physical and chemical properties which are created after melioration do not encourage the restoration of solonetzic process. The solonetzic process in meadow-steppe solonetzes of dry steppe and, especially, forest steppe zones is active at the present moment. The melioration improves the properties of these soils, but it is insufficient for the destruction of physical and chemical conditions favourable for restoration of solonetzic process. The difference in post-meliorative development of solonetzes is stipulated by the initial degree of manifestation of solonetzic process in virgin soils at the present.